2000
DOI: 10.1097/00001756-200011270-00053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain-derived neurotrophic factor and neurotrophin-3 on expression of mRNAs encoding c-Fos, neuropeptides and glutamic acid decarboxylase in cultured spinal neurons

Abstract: There is growing evidence suggesting that neurotrophins have modulating effects on the pain signaling system at spinal levels. In order to determine whether neurotransmitter expression is modulated in response to the elevation of neurotrophins, the changes in c-fos, neuropeptide and glutamic acid decarboxylase (GAD) mRNAs expression was evaluated after BDNF or NT-3 was applied to cultured spinal neurons. Reverse transcription polymerase chain reaction analysis revealed that BDNF induced a significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…According with our results, the up-regulation of the BDNF mature protein has been observed in the ACC during inflammatory pain. 27 In this view, our results suggest that the interplay between BDNF and dynorphin may also occur in an in vivo model of neuropathic pain, precisely at cortical level. Relative gene expression was calculated by the Delta-Delta Ct (DDCt) method and normalized to the reference gene Gapdh.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…According with our results, the up-regulation of the BDNF mature protein has been observed in the ACC during inflammatory pain. 27 In this view, our results suggest that the interplay between BDNF and dynorphin may also occur in an in vivo model of neuropathic pain, precisely at cortical level. Relative gene expression was calculated by the Delta-Delta Ct (DDCt) method and normalized to the reference gene Gapdh.…”
Section: Discussionmentioning
confidence: 56%
“…[19][20][21] The brain-derived neurotrophic factor (BDNF) is an important modulator of neuropathic pain. 27 Neuroimaging studies revealed that morphological and functional changes are induced by neuropathic pain in several brain regions. 24,25 Moreover, rats subjected to chronic constriction injury (CCI) showed typical neuropathic pain signs, together with a higher BDNF immunoreactivity in the ipsilateral dorsal horn.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NT-3 has been shown to induce c-fos (Marsh & Palfrey, 1996;Nonomura et al, 1996), with a time-course relevant to our study. More specifically, in neuronal cultures treated with NT-3 the levels of c-fos mRNA had increased by 3 hr and the increase was maintained up to 6 hr (Bilsland & Harper, 1998;Kim, Lee, Kim, & Cho, 2000). Another possible molecule that could mediate the increase in Fos expression may be the transcription factor pCREB, the increase of which precedes that of Fos, being observed at 4 hr following ''handling'' on PND1 (Garoflos, Stamatakis, Mantelas, Philippidis, & Stylianopoulou, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interneuron development is considered neurotrophin-dependent as many cells express trkB receptors (Gorba & Wahle, 1999). TrkB signalling promotes, in particular, interneuronal synaptogenesis (Huang et al, 1999;Marty et al, 2000;Seil & Drake-Baumann, 2000) and in¯uences inhibitory markers, as in dissociated cultures of cortex, striatum, substantia nigra and spinal cord, GAD-67 mRNA expression, GAD activity and GABA uptake are increased by trkB ligands (Widmer & Hefti, 1994;Carnahan & Nawa, 1995 for review;Spenger et al, 1995;Arenas et al, 1996;Kim et al, 2000). Furthermore, neuronal activity regulates cortical inhibitory markers.…”
Section: Introductionmentioning
confidence: 99%